Marta López Vilar (ed.) (2023), Voces africanas III: Encuentros. Madrid: Sial/ Casa de África, 193 págs. - Cuenca Corrales, Laura (Africanías. Revista de Literaturas, 2024)
Review of the book “Voces africanas III: Encuentros” by editor Marta Lopez Vilar and publisher Sial / Casa de Africa, published in 2023, with 193 pages.